An Archaeology of Abundance : Reevaluating the Marginality of California's Islands - Thompson, Victor D.; Erlandson, Jon; Fauvelle, Mikael; Gill, Kristina, 1982- (Book collections on Project MUSE., 2019)
This volume focuses on the archaeology and historical ecology of a series of islands located off the Pacific Coast of Alta and Baja California, from the Channel Islands to Cedros Island.